HAKIKAT MENYENTUH MUSHAF AL-QUR’AN(Analisis Komparasi Tafsir Ahkam Al-Quran Karya Al-Kiya Al-Harrasi dan Tafsir Al-Misbah Karya Muhammad Qurais Shihab) - Lailatul Mu'jizat, Lailatul Mu'jizat; Mu'jizat, Lailatul (Muqaranah, 2024)
This study aims to conduct a comparative analysis of the views of Qurais Shihab in his tafsir Al-Misbah and al-Kiya al-Harrasi in his tafsir work, Ahkam Al-Quran, on the important issue of the essence of touching the mushaf of the Qur'an. The main focus of this research is the interpretation of Surah Al-Waqiah: 79, which is frequently cited in discussions regarding the conditions of cleanliness and purity when interacting with the Qur'an. To explore this topic, the research employs a muqarran (comparative) approach, focusing on the views of both scholars regarding the verse, along with an analysis of their interpretations and the background of each mufassir. The findings of this study show that, although both Qurais Shihab and al-Kiya al-Harrasi belong to the Shafi'i school of thought, there are differences in their perspectives on the interpretation of this verse. Qurais Shihab, in line with the views of the majority of scholars and the predominant Shafi'i followers in Indonesia, emphasizes the importance of purity when touching the mushaf but allows exceptions in cases of necessity. On the other hand, al-Kiya al-Harrasi, although also a follower of the Shafi'i school, adopts a stricter and more conservative approach, influenced by his adherence to his madhhab, insisting that one may not touch the mushaf except in a state of purity. In his tafsir, al-Harrasi tends to reject other views, highlighting the rigidity of his interpretation on this issue. This research provides deeper insight into the diversity of views within the Islamic tafsir tradition, especially concerning the issue of cleanliness and purity when interacting with the Qur'an. Additionally, this study serves as an important reference for the Muslim community, as it demonstrates how social, cultural, and religious factors can influence the interpretation of the Qur'an.